COVID-19 outbreak effects on leadership, job satisfaction and turnover intention: A mediating model of Indonesian banking sector - Tedi, Hidayat; Rahmi, Fahmy; Dessy, Kurnia Sari; Mergeresa, Fineke; Fernando, Yudi (Penerbit Universiti Malaysia Pahang, 2021)
This peper aims to determine and analyze the direct effect of transformational and transactional leadership on turnover intention, and indirect effect which is mediated by job satisfaction amid COVID 19 Pandemic at the banking sector. As many 153 permanent employees, including staff, supervisors, ass. manager, and division manager were participated. The results showed that transformational leadership has a positive but insignificant effect on turnover intention, while transactional leadership has a negative and significant affect turnover Intention. Furthermore, through mediating impact of job satisfaction, the effect of transformational leadership became negative and significant on turnover intention. Meanwhile, job satisfaction was significantly in line and strengthens the effect of transactional leadership on turnover intention at the banking sector amid COVID 19 Pandemic.